Ability Performance Misalignment in WAEC Mathematics Examination Outcomes: A Quantitative Explanatory Study in North-East Nigeria - Hassan Muhammad; Philip Issa Tsado; Ahmed Rufai Tete; Momozuku Umaru Salihu; Nura AY Musa (Darul Yasin Al Sys, 2026)
This study investigates ability–performance misalignment in West African Examinations Council (WAEC) Mathematics examination outcomes in northeastern Nigeria. A quantitative explanatory cross-sectional design was employed using archival data from public senior secondary schools to examine discrepancies between classroom-based achievement and performance in a high-stakes external examination. The findings revealed that a substantial proportion of students exhibited ability–performance misalignment: some students with high classroom performance obtained low scores in the WAEC Mathematics examination, whereas some students with low classroom performance achieved comparatively high examination scores. Test anxiety, self-efficacy, and inconsistent assessment practices significantly contributed to this misalignment. These findings suggest that WAEC Mathematics examination results may not always accurately represent students’ mathematical achievement and highlight the need to reconsider how high-stakes assessment outcomes are interpreted and used in educational decision-making. The study contributes to the assessment literature by emphasizing the importance of integrating affective, instructional, and contextual factors when evaluating student performance and formulating assessment policies.